CLASSIFICATION OF ORNAMENTAL GLAZED CERAMICS OF DERBENT OF THE END OF THE 8th-10th CENTURIES (ON THE MATERIALS OF EXCAVATIONS 27 AND 33) - Kuzeeva, Zuhra Z. (History, Archeology and Ethnography of the Caucasus, 2020)
The article is devoted to the classification analysis of the glazed ceramics of Derbent, revealed from the materials of archeological excavations (digs 27 and 33), carried out in 2014-2015 in the territory of the city. The time-frame of the study is likely set in the end of the 8th (possibly 9th)-10th century. The relevance of the subject is characterized by the importance of studying glazed ceramics of Derbent as a source valuable information (historical-cultural and socio-economic interactions of Derbent with a wide range of countries of the near and far abroad).The paper considers the typology of the glazed ceramics of Derbent of the end of the 8th-10th centuries on the basis of modern methodological work, consisting of three main approaches to the study of any ceramics: the study of technology along with the morphology and décor of ware. All ceramics under study, consisting of fragments of rims, bodies, bottoms and handles of vessels, is part of one bigger category – household ware. This category is divided into four sections, which are based on the analysis of the clay color (red clay, beige-pink clay, brown clay, beige clay ceramics), determining the technology of ware manufacture. Based on the presence or absence of engobe on ceramics, each section composes of two sub-sections. The next division is the groups that are formed according to the degree of transparency of the glaze: transparent ceramics, semi-transparent and opaque enamel. Within some groups, four subgroups are additionally distinguished, determined by the color of the glaze. According to the features of the additional decor, the types (overglaze, underglaze ornament) and subtypes (painting, engraving, combination of painting with engraving, relief ornament) of ceramics are distinguished. Thus, the characteristics of the glazed ceramics of Derbent from these excavations include: category, sections, sub-sections, groups, subgroups, types, subtypes.The classification principle used demonstrates the development of the production technology of this type of ceramics (features of burning, the development of chemical production, the development of the technology for obtaining a glazed layer on ceramics, etc.). These data make it possible to obtain objective dating of ceramic samples and accurate picture of the development of the glazed ware manufacture.
Keywords: classification; early glazed ceramics; Derbent; pottery; import; Shamkir; Nishapur.